Bioactive compounds and antioxidant potential in fresh and dried Jaffa® sweeties, a new kind of citrus fruit - Gorinstein, Shela; Haruenkit, Ratiporn; Park, Yong Seo; Jung, Soon Teck; Zachwieja, Zofia; Jastrzebski, Zenon; Katrich, Elena; Trakhtenberg, Simon; Belloso, Olga Martin (My University, 2004)
Bioactive compounds in the edible parts of fresh and dried Jaffa® sweeties, a new kind of citrus fruit, were analysed and their antioxidant capacities were assessed. Antioxidant-rich fractions were extracted from fresh and dried sweeties with 1.2 M HCl in methanol/water (1:1 v/v), and the antioxidant activities of these extracts were evaluated. Using the β-carotene/linoleate model system, the extracts from equivalent quantities of fresh and dried sweeties showed 89 and 87% antioxidant activity respectively. Similarly, using the DPPH radical-scavenging method, the extracts showed 87 and 85% antioxidant activity respectively. The best correlations were between caffeic acid content and β-carotene and DPPH antioxidant activity values (r = 0.9849 and 0.9798 respectively, p = 0.005). Both fresh and dried sweeties are bioactive natural products; when fresh fruits are not available, properly dried sweeties could be used as a substitute. © 2004 Society of Chemical Industry.
Keywords: Antioxidant compounds; Antioxidant potential; Fresh and dried sweeties